Temperature effect on the porosity of hydroxyapatite scaffolds and its use in tissue engineering - Vareska Lucero Zarate-Córdova; Mercedes Teresita Oropeza-Guzmán; Eduardo Alberto López-Maldonado; Ana Leticia Iglesias; Theodore Ng; Eduardo Serena-Gómez; Graciela Lizeth Pérez-González; Luis Jesús Villarreal-Gómez (Revista de Ciencias Tecnológicas, 2020)
The search for a suitable bone replacement is of great importance due to the difficulty to use autologous transplants. Hence, the objective of this work is to compare the temperature effect on the porosity and average pore diameter of hydroxyapatite porous scaffolds fabricated by the salt leaching method.  Hydroxyapatite porous scaffolds fabricated by the salt leaching technique were sintered from ~150 to 1000 °C. Synthesized hydroxyapatite was assessed by X-ray diffraction (XRD). Zeta potential at different temperatures was evaluated. Specimens were characterized using scanning electron microscopy (SEM) and Raman analysis. The results showed that significant porosity (57%) and pore size (49 µm) occurred with a thermal treatment above ~ 850 °C for scaffolds that were pre-sintered at 1050 °C.